Peran Kompetensi Dan Pengembangan Karir: Dampaknya pada Kinerja Karyawan - Olivia Melinda Putri; Ardianus Paulus (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to investigate the influence of competence and career development on employee performance at PT Bumi Pembangunan Pertiwi Madiun, Building Materials Division. The research was conducted using a quantitative approach with a causal design. The population consisted of 90 employees, and due to the relatively small number, a saturated sampling technique was applied, resulting in 90 distributed questionnaires. From these, 75 valid responses were analyzed using multiple linear regression. The findings reveal that competence has a positive and significant effect on employee performance, as indicated by a regression coefficient of 0.206 and a significance level of 0.004. Similarly, career development demonstrates a stronger positive and significant effect, with a regression coefficient of 0.777 and a significance level of 0.000. The coefficient of determination (R²) of 0.60 indicates that competence and career development together explain 60% of the variance in employee performance, while the remaining 40% is influenced by other factors such as motivation, compensation, or organizational culture. These results emphasize that while competence is essential as a foundation for effective performance, career development plays a more dominant role in motivating employees and enhancing their contributions.